BS6 Deciphering the local immune lanscape in atrial fibrillation: the role of tissue-resident T cells. (6th June 2022) - Vyas, Vishal; Sandhar, Balraj; Finlay, Malcolm; Longhi, Paula
Abstract : Introduction: Systemic markers of inflammation strongly correlate with an increased risk of atrial fibrillation (AF). However, the local immune drivers of this increased AF risk remain poorly defined. Recently, a wealth of imaging data has established the volume of adipose tissue overlying the heart, epicardial adipose tissue (EAT), as an independent risk factor for all forms of AF. However, the immune profile of EAT driving this increased AF risk again remains undefined. Currently, human tissue studies are sparse with patients typically poorly matched for baseline clinical characteristics. This study sought to systematically define the immunological signature of EAT in a propensity-matched cohort of cardiac surgical patients with a prior history of AF and those in sinus rhythm. Methods: Adult patients with an established history of AF and those with no prior history of AF undergoing cardiac surgery were recruited to undergo EAT, blood and subcutaneous adipose tissue (systemic and adipose tissue controls) sampling. Patients were propensity-matched to ensure baseline clinical variables were similar across the groups. The tissue samples were immediately taken to the laboratory for immune cell isolation, flow cytometry and T lymphocyte cell stimulation assays. Bulk EAT RNA sequencing analysis was performed on a cohort of patients to determine whole tissue RNA expression changes and in 2 patients paired EAT and right atrial appendage (RAA) tissue samples underwent single-cell RNA sequencing with proteomic analysis alongside T-cell receptor sequencing. Results: A cohort of 44 propensity-matched patients was identified (table 1). T lymphocytes were the predominant immune cell type and T cell subset analysis in a sub-cohort of 18 patients revealed a highly significant increase in both EAT-resident CD4+ (p<0.05) and CD8+ (p<0.001) memory T cell populations in AF patients (figure 1). T cell stimulation assays demonstrated a highly significant correlation with the proportion of tissue-resident memory (TRM) CD4+ T cells in EAT and the pro-inflammatory cytokines interferon-γ (p=0.0072) and interleukin-17 (p=0.0042) [figure 2]. In contrast, similar absolute numbers of other immune cell types in the EAT were observed between the two groups while bulk RNA sequencing analysis demonstrated broadly similar immune mediator expression levels between the groups. On a single cell level, similar immune cell clusters were observed between the EAT and RAA while T cell receptor sequencing confirmed the same T cell clones to be present in the RAA as the EAT. Conclusions and Implications: AF carries a unique EAT-resident T cell signature which correlates with the production of the pro-inflammatory cytokines interferon-γ and interleukin-17. Single-cell RNA-sequencing analysis confirms EAT to be the immune reservoir of the heart and EAT sampling can provide an accurate readout of the immune landscape of the underlying cardiac tissue. Targeting this local resident T cell population may unlock a novel angle in the management of the inflammatory and fibrotic components of AF genesis.